Consumer Trust in Internet Shopping: An Empirical Investigation. Issue 2 (December 2016) - Tuteja, Geetu; Gupta, Shashank; Garg, Vaishali
India has seen a tremendous growth in the number of Internet users in the last decade. Despite of the increase in the number of Internet users, the penetration rate of Internet shopping in the country remains low. Hence, this article focuses on building a model around the factors that are responsible for lack of trust in Indian consumers on Internet shopping and unveiling their effect on the consumers' buying intention. Confirmatory factor analysis (CFA) and structure equation modelling (SEM) with AMOS 20.0 was used to confirm factor structure and to perform second-order SEM on the 5-point Likert scale proposed model tested empirically on a sample of 549 individuals. Our research indicates that there are various antecedents like brand orientation, website design, prior online purchase experience, quality orientation, perceived risk, perceived security control, perceived privacy control, perceived integrity, perceived competence, third-party integration and legal framework which affects consumer trust in Internet shopping which is positively associated with an intention to buy. However, the purchase intention of Indian consumers is influenced by the trustworthiness dimension of the model which depends on the factors affecting the consumer trust in e-shopping.